Asymmetrical accommodation in hyperopic anisometropic amblyopia. Issue 6 (19th October 2017) - Toor, Sonia; Horwood, Anna M; Riddell, Patricia
Abstract : Background/aims: To investigate the presence of asymmetrical accommodation in hyperopic anisometropic amblyopia. Methods: Accommodation in each eye and binocular vergence were measured simultaneously using a PlusoptiX SO4 photorefractor in 26 children aged 4–8 years with hyperopic anisometropic amblyopia and 13 controls (group age-matched) while they viewed a detailed target moving in depth. Results: Without spectacles, only 5 (19%) anisometropes demonstrated symmetrical accommodation (within the 95% CI of the mean gain of the sound eye of the anisometropic group), whereas 21 (81%) demonstrated asymmetrical accommodation. Of those, 15 (58%) showed aniso-accommodation and 6 (23%) demonstrated 'anti-accommodation' (greater accommodation for distance than for near). In those with anti-accommodation, the response gain in the sound eye was (0.93±0.20) while that of the amblyopic eye showed a negative accommodation gain of (−0.44±0.23). Anti-accommodation resolved with spectacles. Vergence gains were typical in those with symmetrical and asymmetrical accommodation. Conclusion: The majority of hyperopic anisometropic amblyopes demonstrated non-consensual asymmetrical accommodation. Approximately one in four demonstrated anti-accommodation.